Thermal mathematical model of semiconductor devices for measurement of current-voltage characteristics by pulse method - Yermolenko Ye. O.; Bondarenko O. F.; Baranov O. M. (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature, 2012)
The thermal mathematical model is used to estimate self-heating of semiconductor devices of various types during current-voltage characteristics measuring by the pulse method. The influence of self-heating on electrical parameters of semiconductor devices is analyzed. The recommendations for determination of values of measuring pulse sequence parameters are formulated to minimize self-heating of semiconductor structure.